Default distal radial approach for all coronary procedures – a prospective study. (3rd October 2022) - Pati, P K; Arstall, M; Pati, A
Abstract: Background: Radial artery approach for coronary interventions has substantially improved the outcome especially in acute coronary syndrome patients. However, radial artery occlusion is the achilles' heel of such an approach. Purpose: To obviate such problems, distal radial artery (DRA) approach is evolving but technical challenge is the small size of the artery. We looked at the feasibility, safety and advantages of it. Methods: Patient population included any patient requiring a diagnostic or percutaneous coronary interventions (PCI) in our catheterization laoratory from March 2020 to March 2022. A primary operator performed all procedures as default, if the patient had a palpable DRA. After local anaesthesia infiltration, using seldinger technique and micropuncture kit, 5 to 7F hydrophilic sheaths were introduced and a cocktail of verapamil and heparin was given routinely. Sheaths were removed immediately after procedure but dedicated side specific compression devices were used but removed 45 min after diagnostic and 2 hours after PCI. Clinical patency of radial artery was assessed at discharge and follow up. Results: A total of 682 procedures were performed (50% were diagnostic). Out of all PCIs 59% were for ACS). Elective PCIs included very complex cases including PCI for bifurcation, left main and rota assisted complex PCIs. 651 patients had right distal radial approach and 28 had left. Mean age of patients were 66.8±12.9 years (26 to 97). Females constituted 218 (32%). Mean time from 1st needle puncure to successful vascular access took 1.2±0.8 min (20 sec to 6 min). Average attempts to obtain successful vascular access was 1.3±0.7 (1 to7 attempts). There were 15 failures (2%) to obtain DRA access requiring change over to 6 ipsilateral radial, 2 ulnar, 4 contralateral distal radial, 2 femoral and 1 brachial access. Interestingly, in 5 different occaisions previous procedure related occluded radial arteries were recanalized through this access. Most importantly, no case of radial artery occlusion was encountered at discharge or at follow up by clinical examinations. No other vascular complications were encountered except mild transient bruising in 6 cases and early small hematoma in 3 cases. Patient's comfort, nursing staffs' satisfaction and trend towards early discharges were also noticed. There was a distinct improvement in obtaining faster access with lower failure rates by the operator after initial 90, especially after 150 procedures. Conclusions: A default approach through distal radial artery in anatomical snuff box for all coronary interventions is feasible, safe and possibly superior to conventional radial access with better patient comfort and caring staff's satisfaction. Though learning curve is longer and more challenging, success rates were much higher and vascular access was faster after initial phase. Clinically radial artry occlusion was not seen but needs further study and more objective evidence. Funding Acknowledgement: Type of funding sources: None.